Calvaria Critical Size Defects Regeneration Using Collagen Membranes to Assess the Osteopromotive Principle: An Animal Study - Bizelli, Vinícius Ferreira [UNESP]; Ramos, Edith Umasi [UNESP]; Veras, Allice Santos Cruz [UNESP]; Teixeira, Giovana Rampazzo [UNESP]; Faverani, Leonardo P. [UNESP]; Bassi, Ana Paula Farnezi [UNESP] (MDPI, 2022)
Guided bone regeneration (GBR) is a common practice in implantology, and it is necessary to use membranes in this process. The present study aimed to evaluate the osteopromotive principle of two porcine collagen membranes in critical-size defects at rats calvaria. Ninety-six Albinus Wistar rats were divided into BG (positive control), JS, CS, and CG (negative control) groups and were sacrificed at 7, 15, 30, and 60 days postoperatively. The samples were assessed by histological, histometric, immunohistochemical, and microtomographic analyses. More intense inflammatory profile was seen in the JS and CS groups (p < 0.05). At 60 days, the JS group showed a satisfactory osteopromotive behavior compared to BG (p = 0.193), while CS did not demonstrate the capacity to promote bone formation. At the immunohistochemical analysis, the CS showed mild labeling for osteocalcin (OC) and osteopontin (OP), the JS demonstrated mild to moderate for OC and OP and the BG demonstrated moderate to intense for OC and OP. The tridimensional analysis found the lowest average for the total volume of newly formed bone in the CS (84,901 mm2), compared to the BG (319,834 mm2) (p < 0.05). We conclude that the different thicknesses and treatment techniques of each membrane may interfere with its biological behavior.
Keywords: bone regeneration; inflammation; membranes